EFFECT OF ALBUMIN SOLUTION CONCENTRATION ON THE CRYSTALLIZATION PROCESS AND CRACK FORMATION (Scientific journal of the Fergana State University, 2025)
This study investigates the crystallization processes of albumin solutions at different concentrations. Albumin solutions with concentrations of 5%, 10%, and 20% were dropped onto glass surfaces, and their crystallization time, crack formation, and the complexity of crack patterns were analyzed. The findings enhance the understanding of protein crystallization properties and have applications in biomedical and diagnostic fields.